Organization of Solving Problems in the Module "Linear Optics" of General Physics Based on Modern Pedagogical Technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
In this article, there is proposed a method for solving the problems of the theme "Light return and fracture" in the general physics module "Linear optics" using new pedagogical technologies.